Subminiature panel (SMA-P) coaxial sensor for the determination of moisture content of mango cv. Chok Anan - Noradira Suhaime,; Masniza Sairi,; Zulkifly Abbas,; Nur Biha Mohamed Nafis,; Zaulia Othman,; Amir Syariffuddeen Mhd Adnan,; Amir Redzuan Shamsulkamal,; Ten, Seng Teik (Penerbit Universiti Kebangsaan Malaysia, 2019)
The research describes the development of a simple, cheap and efficient open-ended coaxial sensor for the determination of moisture content of Chok Anan mango during fruit ripening from week 5 to week 17. The sensor was a modification of a standard subminiature panel (SMA-P). The finite element method was used to calculate the numerical values of the reflection coefficient. The reflection coefficient of the sensor was measured using a Microwave Network Analyzer in the frequency range from 1 to 4 GHz. The actual moisture content was obtained using standard oven drying method. A calibration equation was obtained to predict moisture content from the measured reflection coefficient at 1 GHz with accuracy within 1.5%. The results indicate that the amount of m.c. in Chok Anan mango can be determined with excellent accuracy using a SMA-P coaxial sensor as an OEC sensor.